Bottom‐Up Assembly of DNA–Silica Nanocomposites into Micrometer‐Sized Hollow Spheres. Issue 48 (18th October 2019) - Hu, Yong; Grösche, Maximilian; Sheshachala, Sahana; Oelschlaeger, Claude; Willenbacher, Norbert; Rabe, Kersten S.; Niemeyer, Christof M.
Abstract: Although DNA nanotechnology has developed into a highly innovative and lively field of research at the interface between chemistry, materials science, and biotechnology, there is still a great need for methodological approaches for bridging the size regime of DNA nanostructures with that of micrometer‐ and millimeter‐sized units for practical applications. We report on novel hierarchically structured composite materials from silica nanoparticles and DNA polymers that can be obtained by self‐assembly through the clamped hybridization chain reaction. The nanocomposite materials can be assembled into thin layers within microfluidically generated water‐in‐oil droplets to produce mechanically stabilized hollow spheres with uniform size distributions at high throughput rates. The fact that cells can be encapsulated in these microcontainers suggests that our concept not only contributes to the further development of supramolecular bottom‐up manufacturing, but can also be exploited for applications in the life sciences. Abstract : Hierarchically structured composite materials made from silica nanoparticles and DNA polymers (red) can be self‐assembled by the clamped hybridization chain reaction into thin layers within microfluidically generated water‐in‐oil droplets to produce mechanically stabilized micrometer‐sized hollow spheres that hold potential for applications in the life sciences.